ISO 14000 environmental management - Goetsch, David L.; Davis, Stanley B. (Upper Saddle River, New Jersey : Prentice-Hall, 2001)
he only complete book on ISO 14000 written as a practical resource and how-to guide, this book provides a step-by-step model for understanding the ISO 14000 standard. Filling the void for a book related to environmental protection and management, it effectively translates the often-confusing requirements into understandable language. Topics covered include the background of ISO 14000, decoding and implementing ISO 14000, requirements of ISO 14000, the Environmental Management System (EMS), EMS Documentation, registration and the audit process, EMS performance improvement and other ISO standards, issues, and developments. For environmental ISO 14000 professionals, as well as mangers and supervisors of organizations with environmental concerns.
1. Background of ISO 14000 and Why It Exists. -- 2. Decoding ISO 14000. -- 3. Requirements of ISO 14000. -- 4. The Environmental Management System (EMS). -- 5. EMS Documentation. -- 6. Registration and the Audit Process. -- 7. EMS Performance Improvement. -- 8. Implementing ISO 14000: Steps to Registration. -- 9. Other ISO Standards, Issues, and Developments. -- 10. ISO 14000 Checklist. Appendix A: ISO Member Body Roll (Full Members).
Includes index.
Keywords: PRODUCTION MANAGEMENT -- ENVIRONMENTAL ASPECTS